Professor Sven Hernberg, 1934–2019 - Rantanen, Jorma (Scandinavian Journal of Work, Environment & Health, 2019)
On 10 June 2019, the occupational health community received sad news on the passing of Professor Emeritus Sven Hernberg, MD, PhD, specialist in occupational medicine and Scientific Director of the Finnish Institute of Occupational Health (FIOH). Sven died at the age of 85 in Helsinki, Finland. Born in Helsinki, Sven completed his medical studies at the University of Helsinki and served in FIOH for 33 years. He began his residency in occupational medicine in FIOH’s Department of Occupational Medicine in 1960, and specialized in occupational medicine in 1964, obtained his PhD in the toxicology of lead in 1967, and served as an Adjunct Professor at the University of Helsinki’s Medical Faculty from 1970 to 1999. His main career comprised dual positions: Director of FIOH’s Department of Epidemiology and Biostatistics, 1972–1993, and Scientific Director of FIOH, 1974–1993. Sven published about 300 research articles, books, and book chapters, covering an immense number of different types of occupational exposures and outcomes. His contributions to research on occupational epidemiology were immeasurably important. As Scientific Director, he contributed to drawing up FIOH’s first ever multidisciplinary research strategy and took the lead role in its implementation, making FIOH one of the leading institutes of occupational health research. In addition to lead, mercury, cobalt, and carbon disulphide, Sven’s research covered a wide range of exposures such as diphenyl, industrial solvents, formaldehyde, wood dusts, chlorophenoxy herbicides, chlorophenols, work with video display units, asbestos, silica, and foundry work. He used a full range of epidemiologic methods, developed tests and strategies for biological monitoring, initiated several preventive actions, and demonstrated their impact in long-term follow-up studies. The practical impact of his research changed many industrial practices in Finland to protect workers’ health better. Typically, the statistics on occupational diseases first showed an increase, as a consequence of the active detection of diseases, and then a gradually declining trend as a result of effective prevention. When this was observed, Sven turned to new challenges of occupational health. Sven was highly active in several arenas: Nordic, European, EU, and global. The World Health Organization (WHO) relied on Sven as an expert resource for setting the WHO reference values for lead exposure and the early detection of adverse lead effects. He chaired the historical Expert Committee that launched the new concept of work-related diseases and established the work-relatedness criteria of workers’ health outcomes. Sven also served as an expert to the International Labor Office (ILO) among others by writing chapters for the ILO International Encyclopedia on Occupational Health and Safety. In the mid-seventies, Sven initiated, and together with the leaders of other Nordic Institutes, founded the high-quality Scandinavian Journal of Work Environment & Health. From 1975 to 2000, he served as Editor-in-Chief and, from 2000 to 2004, as Emeritus Editor. Sven followed clear principles in his editorial policy – only high-quality, relevant, and new results passed his scrutiny. In this respect, Sven was a faithful follower of Sir Austin Bradford Hill, whom he often cited: "The reader can evaluate a study only if the researchers give sufficiently detailed descriptions of its design, materials, and methods". He never complained of the workload in addition to his other responsibilities because editing the Journal was a great joy for him. When looking back at decades of the Scandinavian Journal of Work Environment & Health, very logical tracks are visible: continuous quality improvement not only for scientific content but also for coverage of substance – according to the changing problems of the workplace and the environment – and expansion of dissemination worldwide. The modern design and layout of the Journal was an important part of this development. Thanks to Sven and his successors, the Journal today represents elegance in outlook, strength in scientific content, and clarity in expression, with a 2018 impact factor of 3.491. Sven stated the following in his 1995 editorial on the occasion of the Journal`s 20th anniversary: “A modern journal, especially one in the applied field of occupational health, should do its best to meet these challenges by helping its readership by collecting and distributing the essentials of new knowledge in an easily accessible form. This approach calls for a deviation from the publishing policy and contents of what has been known as the "classical" or "typical" scientific journal”. Sven was invited as a member of the editorial boards of several international scientific journals, including the editorial board of the American Journal of Industrial Medicine and the advisory board of The Lancet. Sven was a popular and highly respected educator as an Adjunct Professor at the University of Helsinki, and he lectured medical students and postgraduates in other Finnish universities as well as at FIOH. He organized epidemiology courses in FIOH, the Nordic fora, and at the WHO and trained a whole generation of epidemiologists in occupational health. He wrote textbooks on epidemiology and tutored several PhD students. He also trained junior experts in scientific writing and scientific presentation; his courses became popular also among advanced experts. Sven was invited to be a member of several high-level domestic and international scientific bodies, such as the Finnish Academy of Technical Sciences, the Swedish Academy of Technical Sciences, the Faculties of Occupational Medicine of the UK and Ireland Royal Colleges of Physicians and the New York Academy of Medical Sciences, to mention just a few. Of all of these, the International Commission on Occupational Health (ICOH) remained close to Sven’s heart throughout his professional career. He was active in three scientific committees: artificial fibers (secretary), toxicology of metals (member), and epidemiology in occupational health (chair). He was elected for full tenures as ICOH officer: Vice President (1981–1987) and President (1987–1993), and from 1993 to 2000 he served as Past President and Board Member. As Vice President, he renewed the system of scientific committees and as President he renewed ICOH`s Constitution, Bylaws, and Code of Ethics, all of which are still valid and have only undergone minor updating amendments. He led the organization of five ICOH Congresses and substantially improved their scientific weight and organizational practices. Sven was appointed Honorary Member of ICOH in 2000 and was honored with the ICOH Centennial Award in 2006. In honoring him, we – his co-workers, colleagues, and friends from our FIOH and ICOH times and the national and global occupational health community – remember Sven Hernberg with the highest respect and gratitude. We learned so much from him. As a scientist and expert, he was creative, intelligent, vigilant and followed the highest professional standards; he was careful and exacting in problem definition, rigorous with methodological criteria, and critical when making inferences. As the professional and institutional leader of FIOH and ICOH, he was fair and attracted the best people to work with him, guiding and encouraging them to find and develop the best of their capacities. As a colleague and friend, he was always trusted, due to his fairness, honesty and highest ethical standards. Sven was a distinguished figure who will remain among the most prominent leaders in our occupational health community. Quoting Mihály Csíkszentmihályi, Sven shared a trait typical of all creative people: they “tend to bring the entire range of human possibilities within themselves”. We express our sincere condolences and sympathy to Sven’s family, his daughter Dr Micaela Hernberg, PhD, his sons Kim and Göran, and his five grandchildren, for the immeasurable loss of their dear father and grandfather.
Keywords: obituary; Sven Hernberg